INTELLECTUAL CAPITAL PENGARUHNYA TERHADAP RETURN ON ASSETS (ROA) PADA PERUSAHAAN SUB SEKTOR OTOMOTIF DAN KOMPONEN DI BURSA EFEK INDONESIA - Cening Ayuni Ratnadi; Gusti Ayu Mahanavami; Ida Bagus Ngurah Wimpascima (Fakultas Ekonomi Universitas Warmadewa, 2021)
Improvements and changes in the business sector make the company believe that intellectual capital is an important component and asset in measuring and evaluating performance among business sectors. This study aims to examine the effect of Intellectual Capital components, namely Value Added Capital Employed (VACA), Value Added Human Capital (VAHU) and Structural Capital Value added (STVA) on Return On Assets (ROA) in automotive sub-sector companies and components on the Stock Exchange. Indonesia. The sampling technique used purposive sampling with a total sample of 5 companies in the automotive and component sub-sector. The data used are financial statements for the period 2015 – 2019 published on the company's official website. The results showed that Value Added Capital Employed (VACA) had a significant positive effect on Return On Assets (ROA) in Automotive and Component Sub-Sector Companies, Value Added Human Capital (VAHU) had a negative and insignificant effect on Return On Assets (ROA). Automotive and Component Sub-Sector Companies and Structural Capital Value Added (STVA) have a positive but not significant effect on Return On Assets (ROA) in Automotive and Component Sub-Sector Companies.